2002
DOI: 10.1053/joca.2002.0819
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of cartilage oligomeric matrix protein (COMP) correlate with radiographic progression of knee osteoarthritis

Abstract: Serum COMP has the potential to be a prognostic marker of disease progression. High COMP levels, persisting over the 3-year study period in the patients with radiographic progression, indicated differences in disease activity detectable throughout the entire follow-up interval.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
103
3
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(111 citation statements)
references
References 30 publications
4
103
3
1
Order By: Relevance
“…The association we observed was not particularly strong but was consistent with expression data comparing normal and OA-affected cartilage (20), the fact that serum levels of COMP are increased in OA (22), and the fact that COMP levels are heritable (34). A meta-analysis including both sets of data, however, showed no evidence of association between knee OA and COMP.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The association we observed was not particularly strong but was consistent with expression data comparing normal and OA-affected cartilage (20), the fact that serum levels of COMP are increased in OA (22), and the fact that COMP levels are heritable (34). A meta-analysis including both sets of data, however, showed no evidence of association between knee OA and COMP.…”
Section: Discussionsupporting
confidence: 80%
“…Prospective studies have shown that elevated serum levels of COMP are observed early in patients in whom chronic knee pain without radiographic OA progresses to radiographic disease (21). An association of serum concentrations of COMP with prevalent OA has also been reported, for COMP alone and in combination with other serum markers (21), and elevated serum levels of COMP may be a marker of rapid radiographic progression (22). Several COMP mutations produce osteochondral dysplasias (Online Mendelian Inheritance in Man, Johns Hopkins University, Baltimore, MD; online at http://www.ncbi.nlm.nih.gov/entrez/dispomim.cgi?idϭ 600310).…”
mentioning
confidence: 99%
“…Conflicting associations were found for the level of keratan sulfate and the level of cartilage oligomeric matrix protein (COMP). With regard to COMP, Bruyere et al (42) found no significant association (OR or P value not provided) in contrast to Sharif et al (24) and Vilim et al (16). Bruyere et al (42) found no significant associations between osteocalcin, pyridinoline, or deoxypyridinoline and progression of knee OA (OR or P values not provided).…”
Section: Resultsmentioning
confidence: 97%
“…as well as in animal models (26,27). We measured serum COMP levels in the experimental groups at 2 weeks and 10 weeks postsurgery (Figure 2a).…”
Section: Resultsmentioning
confidence: 99%